A case study and analysis of VFM campaign through out of home advertising of Airtel Bangladesh Limited - Khan, Md Irfanul Haque (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.